Psychological Pressures And Their Relationship To Functional Performance Among Teachers Of The Institute Of Science And Techniques Of Physical And Sports Activities - Bentoumi Bilal; Kara Said . (sports creativity, 2025)
Abstract : In this research, we have studied the relationship between psychological pressures and performance of university teachers, taking into account the degree of stress experienced by university teachers which can be a real obstacle for teachers in their educational processes, this study aims to identify the relationship between stress and teacher performance. In this study, the descriptive approach was used on a sample of 60 teachers belonging to the Institute of Science and Technology of Physical and Sports Activities of the University of M'sila, selected with an exhaustive survey method, they were asked to answer a questionnaire as a data collection tool. The results show that stressors significantly affect job performance. Suggestions: organization of scientific training on how to fight against stress at work and how to deal with stress. Keywords: Psychological pressures, Functional performance. .